Use of artificial intelligence in criminal law: It´s study and prevention of gender violence in Ecuador and Brazil - López, Nelson Paúl (2023)
This study aims to examine the potential and applications of Artificial Intelligence (AI) in the study and prevention of gender-based violence in Ecuador and Brazil. It discusses the origins of AI and the history of gender violence in both countries, scrutinizing the role of AI predictive models in identifying potentially violent individuals, predicting violent acts, and enhancing state intervention strategies. The objective of the research is to highlight how AI can be an indispensable tool in combating the high prevalence of gender violence in these countries.